Developing a new undergraduate pharmacology core curriculum: The British Pharmacological Society Delphi Method - Lisa Wallace (Pharmacology Research & Perspectives, 2021)
The British Pharmacological Society (BPS) developed a new core curriculum for undergraduate pharmacology degrees. To do this, a modification of the Delphi Process was used. Initially, a pharmacology educator workshop was hosted to explore the core attributes expected of pharmacology graduates. We then developed these discussions into knowledge, skills, and attitudes statements and sent them, in the form of a questionnaire, to our Expert Group, which included pharmacology professionals from across academia and industry. In an iterative process, the Expert Group were asked to rank each statement according to how much they agreed it was a core graduate attribute. Where there was disagreement, statements were modified according to feedback. After three rounds of questionnaires, we had a draft core curriculum which was then finalized through a discussion workshop with the education community. In this workshop, practical aspects of curriculum implementation were discussed and the potential for the Society to develop resources to support it considered. The revised core curriculum is freely available on the Society website: https://www.bps.ac.uk/media-library-assets/library/undergraduate-pharmacology-core-curriculum. Several examples exist of the curriculum making an impact within and beyond the United Kingdom, where it has been utilized in a quality assurance context, as a tool for curriculum review and also to guide building new programs. Through a series of further expert workshops, the BPS Education and Training committee is currently developing more granular learning outcomes to accompany the core curriculum alongside recommended resources to enable delivery. In addition, this expanded curriculum is also being reviewed and updated to ensure it is fully inclusive and represents the diversity of pharmacology educators and learners worldwide.